Morphological, mechanical and rheological properties of nylon 6/acrylonitrile-butadiene-styrene blends compatibilized with MMA/MA copolymers - Araújo, E. M.; Hage, E.; Carvalho, A. J. F. (Springer Nature, 2003)
The morphological, mechanical and rheological properties of nylon 6/acrylonitrile-butadiene-styrene blends compatibilized with MMA-MA [poly(methyl methacrylate-comaleic anhydride)] copolymers were studied. A twin screw extruder was used for melt-blended the polymers and the injection moulding process was used to mold the samples. The main focus was on nylon 6/ ABS blends compatibilized with one MMA-MA copolymer. This copolymer has PMMA segments that appear to be miscible with the styrene-acrylonitrile (SAN) phase of ABS and the anhydride groups can react with amine end groups of the nylon 6 (Ny6) to form graft copolymers at the interface between Ny6 and ABS rich phases. Tensile and impact and morphological properties were enhanced by the incorporation of this copolymer. Transmission electron microscopy (TEM) observations revealed that the ABS domains are finely dispersed in nylon 6 matrix and led to the lowest ductile-brittle transition temperatures and highest impact properties. It can be concluded that the MMA-MA copolymer is an efficient alternative for the reactive compatibilization and can be used as a compatibilizer for nylon 6/ABS blends.© 2003 Kluwer Academic Publishers.
Keywords: Extruders; Graft copolymers; Injection molding; Nylon polymers; Styrene; Transmission electron microscopy; Compatibilizer; Polymer blends